New land microsnails of the genus Gastrocopta (Eupulmonata: Gastrocoptidae) in the semiarid region of Brazil - Silvio Felipe Barbosa Lima; Evandro Cosmo Tomaz de Abreu (Papéis Avulsos de Zoologia)
Abstract In Brazil, Gastrocoptidae Pilsbry, 1918 includes only land microsnails of the genus Gastrocopta Wollaston, 1878. Here, two new species of Gastrocopta are described from the phytogeographic domain of the Caatinga (semiarid scrubland): Gastrocoptajoaoherminioi sp.nov. and Gastrocopta caatinga sp.nov. The shell morphology of G. joaoherminioi sp.nov. differs substantially from native and invasive congeners of Brazil, mainly in the greatly convex whorls as well as in the number and configuration of apertural barriers, which totals 11 very strongly developed teeth (except suprapalatal tooth) that greatly obstruct the region. The shell morphology of G. caatinga sp.nov. has a typical ovoid shape and apertural barriers totaling four teeth that do not obstruct the region (except for the projection of parieto-angular tooth). The new land snails, found in a dense layer of leaf litter on sandy soil at a semi-open dry tropical forest habitat, are compared with congeners from the neotropical region.